Design and Synthesis of Novel Aminoindazole-pyrrolo[2,3-b]pyridine Inhibitors of IKKα That Selectively Perturb Cellular Non-Canonical NF-κB Signalling - Christopher Riley; Usama Ammar; Aisha Alsfouk; Nahoum G. Anthony; Jessica Baiget; Giacomo Berretta; David Breen; Judith Huggan; Christopher Lawson; Kathryn McIntosh; Robin Plevin; Colin J. Suckling; et al. (Molecules, 2024)
The inhibitory-kappaB kinases (IKKs) IKKα and IKKβ play central roles in regulating the non-canonical and canonical NF-κB signalling pathways. Whilst the proteins that transduce the signals of each pathway have been extensively characterised, the clear dissection of the functional roles of IKKα-mediated non-canonical NF-κB signalling versus IKKβ-driven canonical signalling remains to be fully elucidated. Progress has relied upon complementary molecular and pharmacological tools; however, the lack of highly potent and selective IKKα inhibitors has limited advances. Herein, we report the development of an aminoindazole-pyrrolo[2,3-b]pyridine scaffold into a novel series of IKKα inhibitors. We demonstrate high potency and selectivity against IKKα over IKKβ in vitro and explain the structure–activity relationships using structure-based molecular modelling. We show selective target engagement with IKKα in the non-canonical NF-κB pathway for both U2OS osteosarcoma and PC-3M prostate cancer cells by employing isoform-related pharmacodynamic markers from both pathways. Two compounds (SU1261 [IKKα Ki = 10 nM; IKKβ Ki = 680 nM] and SU1349 [IKKα Ki = 16 nM; IKKβ Ki = 3352 nM]) represent the first selective and potent pharmacological tools that can be used to interrogate the different signalling functions of IKKα and IKKβ in cells. Our understanding of the regulatory role of IKKα in various inflammatory-based conditions will be advanced using these pharmacological agents.